2020
DOI: 10.1155/2020/9528014
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Pro-B-Type Natriuretic Peptide and Malnutrition in Patients on Hemodialysis

Abstract: Natriuretic peptides, brain natriuretic peptide (BNP), and N-terminal probrain natriuretic peptide (NT-proBNP) are mainly known as diagnostic markers for heart failure with high diagnostic and prognostic values in the general population. In patients who are undergoing hemodialysis (HD), changes in NT-proBNP can be related to noncardiac problems such as fluid overload, inflammation, or malnutrition and can also be influenced by the dialysis characteristics. The current review aimed to summarize findings from st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…25 Regarding the role of natriuretic peptides, previous studies have identified a potential association between these markers and malnutrition. [26][27][28][29] The association between high concentrations of natriuretic peptides and malnutrition is likely explained by their role as markers of congestion and hence gut oedema, malabsorption, and inflammatory activation. In the context of advanced HF, very-high levels of natriuretic peptides (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Regarding the role of natriuretic peptides, previous studies have identified a potential association between these markers and malnutrition. [26][27][28][29] The association between high concentrations of natriuretic peptides and malnutrition is likely explained by their role as markers of congestion and hence gut oedema, malabsorption, and inflammatory activation. In the context of advanced HF, very-high levels of natriuretic peptides (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, bioelectrical impedance analysis is useful to assess body composition, identify malnutrition and perform close and targeted patient monitoring 25 . Regarding the role of natriuretic peptides, previous studies have identified a potential association between these markers and malnutrition 26–29 . The association between high concentrations of natriuretic peptides and malnutrition is likely explained by their role as markers of congestion and hence gut oedema, malabsorption, and inflammatory activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether NT-proBNP is a marker of volume overload or a marker of left ventricular dysfunction remains unclear. A review article showed that NT-proBNP was correlated with PEW syndrome and inflammation in patients undergoing hemodialysis [28]. In fact, 63.8% of patients with NT-proBNP ≥7200 pg/mL had low SMI and/or inflammation, and 53 patients (66.3%) had low PhA and/or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP is mainly cleared through glomerular filtration by the kidney, which explains the strong correlation between renal function and NT-proBNP levels [ 9 ]. In patients with CKD, besides heart and renal failure, other factors, such as hyperhydration, left ventricular hypertrophy, anemia [ 3 , 10 ], age, inflammation, and malnutrition, can increase the levels of NT-proBNP [ 11 , 12 , 13 , 14 , 15 ]. In these patients, the ratio between the cardiac secretion of NT-proBNP linked to different stimuli and the retention of NT-proBNP due to renal dysfunction is unknown [ 16 ].…”
Section: Introductionmentioning
confidence: 99%